Investigation of Child Abuse Incidence in Akwa Ibom State: The Social Implications and Remedial Measures for Sustainable Development in Akwa Ibom State Communities - Edidiong Linus NKAN; Mfoniso Edet Tom (Researchparks Publishing, 2023)
Child abuse has profound and far-reaching effects on society, impacting individuals, families, and communities. The consequences of child abuse manifest in various dimensions, encompassing physical, emotional, and social aspects, thereby contributing to a range of societal challenges. The study aims to investigate child abuse incidence in Akwa Ibom State, the social implications, and remedial measures for sustainable development in our communities. The emotional toll of child abuse is substantial, leading to mental health disorders, low self-esteem, and difficulties forming healthy relationships. These individual repercussions extend to the societal level as survivors of child abuse may face challenges in education, employment, and overall functioning, perpetuating cycles of disadvantage. The study reviewed the effects of child abuse in society, the cases of child abuse, and the impact of child abuse on sustainable development in Akwa Ibom State communities. In carrying out the study, a descriptive survey design was adopted. The study was carried out in Akwa Ibom State. The targeted population for the study comprised all social scientists in Akwa Ibom State. A stratified random sampling technique was used to select 30 social scientists from 5 local government areas each and this gave a sample size of 150 respondents. The instrument used for data collection was a structured questionnaire titled “Child Abuse and Remedies Questionnaire (CARQ)”. Face and content validation of the instrument was carried out by an expert in test, measurement and evaluation in order to ensure that the instrument has the accuracy, appropriateness, and completeness for the study under consideration. The reliability coefficient obtained was 0.78, and this was high enough to justify the use of the instrument. On this basis, the study concluded that the social implications of child abuse extend beyond individual suffering, impacting the very foundation of our communities. As we reflect on the findings, it becomes evident that sustainable development in Akwa Ibom State hinges on our collective ability to address these challenges comprehensively and with a steadfast commitment to the well-being of our children. The remedial measures adopted include education and awareness programmes, mental health services, legal reforms and enforcement as well as school-based prevention programs. One of the recommendations made was that the government should develop and strengthen support services for both victims and families affected by child abuse. This includes establishing counseling and rehabilitation programs that address the psychological, emotional, and social needs of the victims.